Opioid Consumption Following Outpatient Foot and Ankle Surgery: A Prospective Analysis. Issue 4 (16th October 2019) - Heiman, Erick M.; Wu, Kevin; Idarraga, Alexander J.; Bohl, Daniel D.; Lin, Johnny; Holmes, George B.; Lee, Simon; Hamid, Kamran S.
Category: Prescription Practices Introduction/Purpose: Opioid abuse has recently reached the conscience of the US healthcare system and news cycle. This epidemic is in part propagated by surgeon over-prescription for common procedures. The purpose of this study is to examine postoperative opioid use following outpatient foot and ankle surgery in order to potentially guide prescription patterns of postoperative narcotics. Methods: Patients undergoing outpatient foot or ankle surgery, performed by one of four fellowship-trained orthopedic foot and ankle surgeons from a single institution, were prospectively enrolled from January to November 2018. Subjects were consented to participate in a phone interview within 7 days of their surgery, with subsequent interviews as needed for continued monitoring. Information collected included: age, gender, procedure, smoking status, payor type, analgesic regimen, number of tablets remaining, pain scale, pain control satisfaction, additional analgesic medications taken, reason for stopping opioid medications, and any adverse reactions encountered. Results: A total of 94 subjects were consented to participate. Of these, 11 were lost to follow up and 2 withdrew from the study, leaving 81 (86%) subjects for analysis. The mean (± standard deviation) number of opioid pills prescribed was 52.2 (±16.4; range: 6-80) pills. Subjects were satisfied or somewhat satisfied with their pain control in 91% of cases. On average, 18.4 (±14.9) pills were consumed by subjects, stopping consumption on post-operative day 4.8 (±3.6). There was no statistically significant difference in narcotic medications consumed whether undergoing ankle surgery (16.4, ±13.7) or foot surgery (20.7, ±15.9) (p=0.11). Overall, an average of 34.3 (±19.3) pills remained unconsumed at the completion of narcotic use, equaling a total of 2, 706 excessively prescribed pills in the study cohort. Conclusion: There is a substantial excess of opioid pain medication prescribed to patients for outpatient foot and ankle surgeries, with a wide variation in prescription patterns. Based on our institutional data, a prescription of 35 opioid pills should be sufficient for approximately two-thirds of outpatient procedures and 50 pills should be sufficient for approximately 95% of patients regardless of whether the procedure is for the ankle or foot. This quality improvement assessment has influenced physician practice in our group and prospective follow-up analysis after intervention is warranted.